Predictors of knowledge regarding Ebola virus disease among medical and nursing students in a Nigerian teaching hospital - Balami, Lawan Gana; Ismail, Suriani; Muhamad Saliluddin, Suhainizam; Garba, Sani Hyedima (Medip Academy, 2016)
Background: The Ebola Virus disease is one of the deadliest re-emerging diseases; the 2014 outbreak has been devastating with thousands of deaths resulting in global panic. Methods: A cross-sectional study was conducted involving 423 under-graduate medical and nursing students from University of Maiduguri Teaching Hospital using multi-stage stratified random sampling. Data was collected using a pretested self-administered questionnaire and analyzed using IBM-SPSS version 22. Chi-square was used for association between categorical variables while Spearman’s correlation was used for correlation between continuous variables. Multiple Logistic regressions were used to determine independent predictors of knowledge. Results: Mean knowledge score was 30.4±6.4, only 40.9% had good knowledge. Predictors of knowledge were Age (AOR=1.164, 95% CI=1.07-1.26), Field of study (AOR=4.64, 95% CI=2.33-9.23) and Year of studies (AOR=2.27, 95% CI = 1.06-4.84). Conclusions: There is still poor knowledge regarding this disease and the need for improvements.